(untitled) - Wu, C. Thomas (Boston, 2010)
This book is an introduction to object-first programming using the java programming language. We use be the object-first approach where objects are used from the first sample program. Object-oriented thingking is emphasized and promoted from the beginning. Students learn how to use objects first and then learn how to define their own objects.
Keywords: Lập trình hướng đối tượng ( khoa học máy tính ),Java (Computer program language),Java ( ngôn ngữ chương trình máy tính ),Object-oriented programming (Computer science)